KINETIKA REAKSI TRANSESTERIFIKASI MINYAK KELAPA SAWIT MENJADI METIL ESTER DENGAN KATALIS CaO/ ABU TERBANG BATUBARA - Fiyansah, Toni Okta; Fadarina; Aznury, Martha (Politeknik Negeri Sriwijaya, 2021)
Catalyst CaO from snakehead fishbone with supported by fly ash has advantages for the transesterification reaction process, which include active heterogeneous base properties, low solubility, good mechanical strength, and reusability. This study aims to determine the best catalyst that has the optimum impregnation time and mass of CaO in terms of the transesterification reaction of palm oil into methyl esters. The study includes: prediction of the mechanism according to the experimental data, through the effect of impregnation time and the added mass of CaO on changes in the reaction rate that occur, and the formulation of the final equation for the optimum reaction rate of the catalyst. Prediction of the mechanism that occurs follows the Eley-Rideal mechanism, where the reactant adsorbed on the surface of the catalyst is methanol and reacts with triglycerides (palm oil) to produce methyl esters and glycerol. The results of the study indicate that the greater the impregnation temperature and the added mass of CaO, the greater the rate value. The results showed that the optimum catalyst had an impregnation temperature of 80ÂºC and a mass of CaO 100 grams, with a reaction time of 120 minutes to produce a yield of 98.55%, and a reaction rate of 4.44Ã—10-6 mol/gramcat.